2005
DOI: 10.1007/s10886-005-7106-z
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of the Parasitoid Anagrus nilaparvatae to Rice Volatiles Induced by the Rice Brown Planthopper Nilaparvata lugens

Abstract: Anagrus nilaparvatae, an egg parasitoid of the rice brown planthopper Nilaparvata lugens, was attracted to volatiles released from N. lugens-infested plants, whereas there was no attraction to volatiles from undamaged plants, artificially damaged plants, or volatiles from N. lugens nymphs, female adults, eggs, honeydew, and exuvia. There was no difference in attractiveness between plants infested by N. lugens nymphs or those infested by gravid females. Attraction was correlated with time after infestation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
4
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 37 publications
5
112
4
6
Order By: Relevance
“…These results indicate that the level of infestation by host larvae may be an important factor for E. japonica females to locate plants with host larvae feeding. The effect of host larvae density on infestation duration and attraction was demonstrated in the egg parasitoid Anagrus nilaparvatae (Lou et al, 2005) and the predatory mite Phytoseiulus persimilis (Gols et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the level of infestation by host larvae may be an important factor for E. japonica females to locate plants with host larvae feeding. The effect of host larvae density on infestation duration and attraction was demonstrated in the egg parasitoid Anagrus nilaparvatae (Lou et al, 2005) and the predatory mite Phytoseiulus persimilis (Gols et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This illuminated the Y-tube with a light intensity of 865 lx. For each of the bioassays, 50 adult aphids were tested following established protocols [18] . The aphids were introduced individually into the entry arm.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, thirty-four compounds were selected to investigate the interaction of OBPs with rice plant volatiles (Lou et al, 2005;Sun et al, 2013b). Cnaphalocrocis medinalis OBP2 (CmedOBP2) showed a significant response to host volatiles, whereas CmedOBP3 showed relatively little response to these volatiles (Sun et al, 2016b); our study found that all BdorOBP genes showed low or no response to combined volatile treatments at all tested physiological stages, except the OBP2, OBP5 and OBP1 genes, which were highly expressed.…”
Section: Discussionmentioning
confidence: 68%